Nonlinear analysis and semilinear elliptic problems - Ambrosetti, A. (Antonio); Malchiodi, Andrea; Cambridge eBooks (Cambridge : Cambridge University Press, 2007)
Many problems in science and engineering are described by nonlinear differential equations, which can be notoriously difficult to solve. Through the interplay of topological and variational ideas, methods of nonlinear analysis are able to tackle such fundamental problems. This graduate text explains some of the key techniques in a way that will be appreciated by mathematicians, physicists and engineers. Starting from elementary tools of bifurcation theory and analysis, the authors cover a number of more modern topics from critical point theory to elliptic partial differential equations. A series of Appendices give convenient accounts of a variety of advanced topics that will introduce the reader to areas of current research. The book is amply illustrated and many chapters are rounded off with a set of exercises.
Title from publisher's bibliographic system (viewed on 05 Oct 2015).
Keywords: Nonlinear theories; Differential equations, Elliptic; Electronic books